2016
DOI: 10.1021/acs.energyfuels.6b01398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbonate Decomposition on Normal Spectral Radiative Emittance in the Context of Oxyfuel Combustion

Abstract: To investigate whether the radiative properties of carbonate rich ash layers in oxyfuel combustion systems might be influenced by the carbonate decomposition to the corresponding oxide, the emittance of Sr, Mg, and Ca carbonates is examined. In addition "synthetic coal ashes" were produced from mixtures of CaCO 3 and SiO 2 as well as Fe 2 O 3 and SiO 2 . The mixture ratios of the minerals were varied. All samples were prepared from powders with known particle size fractions of x < 32 μm and 125 < x < 160 μm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…The arithmetic means and the medians are larger for the Fe 2 O 3 -HTC char in the NIR region, which fits to the spectral dependencies described previously. However, the interquartile range and, consequently, the variation are also The larger emissivity of the Fe 2 O 3 -HTC char fits previous results of Gorewoda and Scherer [26] for synthetic coal ash. They found that the total (and below 8 mm, also the spectral) emissivity of Fe 2 O 3 is higher than the total emissivity of SiO 2 .…”
Section: Experimental and Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The arithmetic means and the medians are larger for the Fe 2 O 3 -HTC char in the NIR region, which fits to the spectral dependencies described previously. However, the interquartile range and, consequently, the variation are also The larger emissivity of the Fe 2 O 3 -HTC char fits previous results of Gorewoda and Scherer [26] for synthetic coal ash. They found that the total (and below 8 mm, also the spectral) emissivity of Fe 2 O 3 is higher than the total emissivity of SiO 2 .…”
Section: Experimental and Resultssupporting
confidence: 88%
“…The larger emissivity of the Fe 2 O 3 ‐HTC char fits previous results of Gorewoda and Scherer for synthetic coal ash. They found that the total (and below 8 µm, also the spectral) emissivity of Fe 2 O 3 is higher than the total emissivity of SiO 2 .…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…The decreasing emissivity of fuel particles at increasing temperatures fits to the expected behavior from the literature [12,16,17]. Although there are slight local minima and maxima in the emissivity of both fuels, the trend is clearly shown.…”
Section: Temperature Dependent Emissivity Evaluationsupporting
confidence: 84%
“…Although these linear correlations are not based on any particular theory, the regression parameters, R 2 = 0.784 in case of nutshells and R 2 = 0.956 in case of coal, provide the best fit. The two linear regression functions for nutshell and for coal are as follows: The decreasing emissivity of fuel particles at increasing temperatures fits to the expected behavior from the literature [12,16,17]. Although there are slight local minima and maxima in the emissivity of both fuels, the trend is clearly shown.…”
Section: Temperature Dependent Emissivity Evaluationsupporting
confidence: 72%
“…Oxy-fuel CFB combustion of fuels containing carbonate minerals [48][49][50][51] resulted in smaller CO 2 production due to decreased decomposition of carbonate minerals. The extent of carbonate decomposition was calculated based on the content of CaO, MgO and CO 2 in the ashes; the methodology is described more thoroughly by Arro et al [52].…”
Section: Ashesmentioning
confidence: 99%